ANALYSIS OF THE IMPACT OF ROUTING FLEXIBILITY ON THE PERFORMANCE OF FLEXIBLE SYSTEM - ALI, MOHAMMED (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
The role of flexibility in manufacturing is becoming most important as the pressures due to variety of products are continuously increasing coupled with declining volumes and faster response to customers. This paper deals with implementation of manufacturing flexibility at the shop floor level of the industry under consideration. The main objective of this paper is to compare the performance of existing manufacturing system with that of flexibility based manufacturing system. To achieve the objectives simple demo simulation model of the existing and proposed manufacturing system is built and performance compared. Both these system are compared on the following performance measures i.e., total production and total production time. The introduction of flexibility causes a decrease in makespan time, with maximum reduction in the makespan time occurring when routing flexibility is increased from 0 to 1. Also total production of parts increases with the increase in the level of flexibility.